Genetic Variability, Heritability, Correlation and Path Coefficient Studies for Yield and Yield Components of Some Promising Rice Hybrids - Akter, A; Hasan, MJ; Latif, MA; Kulsum, MU; Biswas, PL; Rahman, MH; Majumder, RR; Lipi, LF; Quddus, MR; Akter, F; Ara, A (Bangladesh Rice Journal, 2020)
Eight promising hybrids along with three checks were evaluated for yield and yield contributing traits to observe their genetic variability, heritability, correlation and path coefficient analysis during T. Aman season 2014. The results indicated that the highest genotypic variance was recorded in spikelet panicle-1 followed by effective tiller m-2. Similarly, the highest phenotypic variances were also found with these two characters. Phenotypic coefficient of variation (PCV) was slightly higher than genotypic coefficient of variation (GCV) for all the traits under this study. Hence, slight differences indicate less or minor environmental influence and greater role of genetic factors on the expression of the traits. High heritability was observed in all the characters studied except effective tiller m-2. Highly significant and positive correlations of grain yield with effective tiller m-2, spikelet panicle-1 at genotypic level were observed. Spikelet fertility was found significant at both genotypic and phenotypic level. Path analysis revealed that spikelet fertility had highly positive direct effect on grain yield followed by effective tiller m-2. On the other hand, spikelet panicle-1 showed positive indirect effect on grain yield. Thus, the results suggested that effective tiller m-2; number of spikelet panicle-1 and spikelet fertility (%) could be considered as effective selection criteria for the development of heterotic rice hybrids. Bangladesh Rice j. 2019, 23(2): 27-34